2017
DOI: 10.1101/176685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole Root Transcriptomic Analysis Reveals a Role for Auxin Pathways in Resistance toRalstonia solanacearumin Tomato

Abstract: Summary 24The soilborne pathogen Ralstonia solanacearum is the causal agent of bacterial wilt, and causes

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…In line with our data, the expression of DR5, a marker gene of the auxin signaling pathway, was strongly induced in root vascular after R. solanacearum GMI1000 infection (Lu et al 2018). Moreover, the dgl1-1 tomato mutant with disordered auxin transport was highly resistant to R. solanacearum (French et al 2018). Together, these data strongly support that auxin signaling plays a negative role in root defense against R. solanacerum.…”
Section: R Solanacearum Causes Genome-wide Transcriptional Reprogramsupporting
confidence: 89%
“…In line with our data, the expression of DR5, a marker gene of the auxin signaling pathway, was strongly induced in root vascular after R. solanacearum GMI1000 infection (Lu et al 2018). Moreover, the dgl1-1 tomato mutant with disordered auxin transport was highly resistant to R. solanacearum (French et al 2018). Together, these data strongly support that auxin signaling plays a negative role in root defense against R. solanacerum.…”
Section: R Solanacearum Causes Genome-wide Transcriptional Reprogramsupporting
confidence: 89%
“…The gene Araip.ZD3PG was predicted to code for auxin response factor, which may involve in the regulation of auxin pathway. Recent reports showed that the repression of auxin pathway improved the resistance to bacterial pathogen (French et al, 2018;Navarro, 2016). The gene Araip.CMC8E might code for calcium-dependent protein kinase, which could perceive changes in intracellular calcium concentrations to transmit defence signal in response to PAMPs and pathogen effectors (Liu et al, 2017;Wang et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…The work of Tarinee et al [59] has shown that the auxin secreted by R. solanacearum is involved in the early stages of infection in tomatoes and accentuates the symptoms of the disease; they have demonstrated that several auxin signaling and transport mutants induce tomato resistance to bacterial wilt. In addition, the work of French et al [60] reported that during in vitro inoculation of R. solanacearum, effector proteins (T3SS and T3E) called type III effectors, whose expression is regulated by the bacterial protein HrpB, are the main determinants of the pathogenicity of the bacterium responsible for the various morphological alterations and the blocking of the growth of the primary roots of host plants with induction of disease symptoms [61].…”
Section: Grammentioning
confidence: 99%